Network analysis of knowledge building on rural extension in Colombia (2016)
Based on the analysis of scientific papers published on rural extension in Colombia since 2010, an interpretive descriptive study was conducted to identify the level of collaboration between authors and institutions in the creation, systematization and dissemination of knowledge in rural extension. Information was gathered from a search in bibliographic databases to identify papers published in rural extension. 50 papers were found. They were organized in a database, and using social network analysis, a review of relational structures and indicators derived from the scientific collaboration between the authors and institutions involved in the publication conducted. Authors from 28 different institutions have participated in the 50 papers identified, 70% of them have been published by researchers working in the same institution. The findings of this study support the conclusion that actors building knowledge on rural extension in Colombia have a limited intra and interinstitutional articulation, making it urgent to strength public policies and incentives to foster relationships between research groups and institutions.